Peran Mufattisy dalam Meningkatkan Kompetensi Pengajar di Madrasah Diniyah Hidayatul Mubtadiin Lirboyo - Luqmanul Hakim; Abbas Sofwan Matlail Fajar (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
The aim of this research is to find out: 1) the planning for observing the teacher in Madrasah Hidayatul Mubtadiin (MHM), 2) the implementation of observing the teacher, 3) the role of mufattisy in improving the competence of teachers in MHM. This research uses descriptive qualitative method with data collection techniques through interviews, observation, and documentation. Analysis techniques with data reduction, exposure, drawing conclusions. Checking the validity of the data with triangulation. The research results were: The planning of observing began with the formation of a team, outlining work procedures, setting observing goals, and creating a control schedule. The implementation of observing involved class visits and taking approaches. The follow-up to observing results included providing guidance and motivation to the teachers. Mufattisy's efforts to improve competence is implemented by scheduling collaborative learning and subject teacher discuss, conducting weekly teacher meetings, and organizing meetings with all teachers and head school, referred to as "temu wicara" (dialogue meetings).